2018
DOI: 10.7196/samj.2018.v108i9.12958
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol marketing and adolescent alcohol consumption: Results from the International Alcohol Control study (South Africa)

Abstract: Background.A complete ban on alcohol advertisements has been proposed for South Africa (SA), but there has been limited local research on the association between exposure to alcohol advertisements and alcohol consumption. Objectives. To examine the role of demographic factors, exposure to alcohol marketing and liking of alcohol advertisements in predicting use of alcohol in the past 6 months among older adolescents in Tshwane, Gauteng Province, SA. Methods. Participants comprised the adolescent sub-sample (N=8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
5
18
0
1
Order By: Relevance
“…Similar to our results, a number of studies have also reported lack of policy restrictive measures and concluded that because of lack of enforcement, some adolescent users were not aware of the existence of such laws and that those who were, noted the lack of enforcement of the same [35,36]. However, this study also highlights the fact that knowledge of restrictive policies is not directly related to abstinence among adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our results, a number of studies have also reported lack of policy restrictive measures and concluded that because of lack of enforcement, some adolescent users were not aware of the existence of such laws and that those who were, noted the lack of enforcement of the same [35,36]. However, this study also highlights the fact that knowledge of restrictive policies is not directly related to abstinence among adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to the ubiquitous presence of alcohol marketing in team sports, both within sporting venues and on television. Studies have consistently linked exposure to alcohol marketing and adolescent alcohol use (Anderson et al, 2009;Morojele et al, 2018) and one systematic review has specifically linked alcohol sports sponsorship to alcohol consumption among young people (Brown, 2016). Due to the association between sports and alcohol consumption, intramurals may be a potential avenue to reach adolescent males and promote safer drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Although alcohol producers often argue that advertising does not influence drinking [34], empirical evidence suggests otherwise. For example, studies in Nigeria [64], Tanzania [65] and South Africa [66] have found that advertising is associated with drinking among young people. A recent South African study also revealed that exposure to alcohol advertising and promotions via SMS and point‐of‐purchase free offers facilitated heavy drinking [67].…”
Section: Key Findingsmentioning
confidence: 99%